Physiological responses of aloe vera to salt stress in coastal sandy soil: Morpho-physiological evaluation for sustainable cultivation - Aprilia, Rennanti Lunnadiyah; Purwanto, Edi; Suryanti, Venty; Rahayu, Muji (Asian Journal of Agriculture and Rural Development, 2025)
This study aims to investigate the morphological and physiological responses of Aloe vera to various levels of salinity and seedling origins when cultivated in coastal sandy soils, which are considered marginal agricultural resources. A randomized factorial design was employed, testing four salinity levels (0, 5, 10, and 20 g/L NaCl) and seedlings sourced from three nurseries (Gunung Kidul, Bantul, Cilacap), resulting in a total of 36 treatment combinations evaluated over a 12-month nursery trial. The results showed that seedling origin had a significant influence on plant development. Seedlings from Gunung Kidul consistently demonstrated the best performance in fresh and dry biomass production as well as physiological stability under salinity stress. Moderate salinity (5–10 g/L NaCl) significantly improved parameters such as leaf length, leaf area, and net assimilation rate, indicating an optimal adaptive window for Aloe vera growth. Conversely, high salinity (20 g/L) reduced stomatal density and leaf number, signaling a physiological stress response. The combination of Gunung Kidul seedlings with 5 g/L NaCl (A1G1) resulted in the best overall plant performance, highlighting the importance of proper seedling selection and salinity management in maximizing productivity. These findings confirm the potential of Aloe vera as a sustainable crop for marginal lands, particularly coastal sandy soils. This study also provides a practical framework for improving yield and stress resilience through appropriate seedling selection and controlled saline irrigation practices. The study contributes to the development of adaptive agricultural systems in saline-prone areas.